'L'essentiel, c'est la contingence': how literature does and does not cope with contingency. Issue 3 (16th March 2018) - Benne, Christian
ABSTRACT: This essay offers a critique of the concept of containing or coping with contingency ( Kontingenzbewältigung ) put forward by a group of German philosophers and intellectuals throughout the 1980s and 1990s. This group put an emphasis on literature, especially story-telling, for thinking about contingency as a characteristic dilemma of modernity. In contrast to their anthropological perspective, I claim not only that different literary genres, periods, and even individual works and readings perform different coping practices in a historically and aesthetically specific manner, but also that literature primarily serves as a means for reflecting on the enactment of a wide variety of coping practices. I demonstrate my theses with three short literary examples (Voltaire, Sartre, contemporary zombie fiction).